Augmented reality based flight assisting system under emergency circumstances - Islam, A.R.M. Rizwan; Era, Sadia Anjum; Joarder, Jubayed Islam; Islam, Md. Rafiu (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.